2022
DOI: 10.1002/adfm.202210456
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ions Confined in Periodic Pores of MOFs to Embed Single‐Metal Atoms within Hierarchically Porous Carbon Nanoflowers for High‐Performance Electromagnetic Wave Absorption

Abstract: Nanocarbons with single-metal atoms (M-SAs) have displayed considerable potential in various fields of application due to high free energy of M-SAs and strong metal-support interaction. However, the uniform dispersion of M-SAs within the whole carbon matrix still remains a great challenge. Herein, Ni-SAs are uniformly dispersed within hierarchically porous carbon nanoflowers (Ni-SA/HPCF) via a spatial confinement of Ni ions within the periodic pores in metal-organic frameworks (MOFs) with a subsequent carboniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…[8,9] High sensitivity, strong detectivity, broad response frequency, and excellent stability EM devices are urgently needed. [10][11][12][13][14][15] The update and iteration of electronic communication, material synthesis, EM response mechanism, and multifunctional integration technology have promoted the development of EM devices in the fields of sensing, detecting, energy storage, triboelectric nanogenerator, information transmission, Joule heating, microwave driving, etc. [16][17][18] For example, Li et al reported microwave-driven robots composed of wave-absorbing sheets and bimetallic sheets, which can realize path control by tuning the polarization direction of microwaves at 2.47 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] High sensitivity, strong detectivity, broad response frequency, and excellent stability EM devices are urgently needed. [10][11][12][13][14][15] The update and iteration of electronic communication, material synthesis, EM response mechanism, and multifunctional integration technology have promoted the development of EM devices in the fields of sensing, detecting, energy storage, triboelectric nanogenerator, information transmission, Joule heating, microwave driving, etc. [16][17][18] For example, Li et al reported microwave-driven robots composed of wave-absorbing sheets and bimetallic sheets, which can realize path control by tuning the polarization direction of microwaves at 2.47 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…9 and Table S2† for comparison. 31,57,58,62,92–99 Both Ni/OMCN-D and Ni/OMCN-S indeed possessed superior comprehensive EMWA performance to those similar EMWAMs in terms of RL max , EAB, thickness, and filler loading. Taking Ni/OMCN-D as an example, the associated mechanisms for the excellent EMWA performance mainly lied in the following aspects (Scheme 2).…”
Section: Resultsmentioning
confidence: 95%
“…It can be seen that 3DOM RFCo-2 shows the best EMW absorption performance among all samples, and its EAB is up to 5.28 GHz, covering almost the whole Ku band (12-18 GHz), which is significantly better than those of similar existing materials (Table S1, ESI †). [10][11][12][27][28][29] In addition, to further investigate the 3DOM RFCo-2 composite, Fig. 4g shows a 2D RL plot of this material for a single thickness in the range of 1.5-5.0 mm and visualizes the maximum EAB and RL min values for different thicknesses.…”
Section: Rl Dbmentioning
confidence: 99%